Development and validation of an online emotional intelligence training program - Durham, Michelle R. Persich; Smith, Ryan; Cloonan, Sara; Hildebrand, Lindsey L.; Woods-Lubert, Rebecca; Skalamera, Jeff; Berryhill, Sarah M.; Weihs, Karen L.; Lane, Richard D.; Allen, John J. B.; Dailey, Natalie S.; Alkozei, Anna; et al. (Frontiers in Psychology, 2023)
Emotional intelligence (EI) is associated with a range of positive health, wellbeing, and behavioral outcomes. The present article describes the development and validation of an online training program for increasing EI abilities in adults. The training program was based on theoretical models of emotional functioning and empirical literature on successful approaches for training socioemotional skills and resilience. After an initial design and refinement process, the completed online program was tested for efficacy in a sample of 326 participants from the general population. Participants were randomly assigned to complete either the EI training program or a matched placebo control training program. Each program involved 10-12 hours of engaging online content. Participants who completed the EI training program showed increased scores from pre- to post-training on standard self-report measures of EI (relative to placebo), indicating self-perceived improvements in recognizing emotions, understanding emotions, and managing the emotions of others. Moreover, those in the EI training also showed increased scores in standard performance-based EI measures, demonstrating an increased ability to strategically use and manage emotions relative to placebo. Improvements to performance measures also remained significantly higher than baseline when measured six months after completing the training. The training was also well-received and described as helpful and engaging. These results suggest that this novel online training program can improve EI and demonstrate sustained gains for up to six months post-training.